2017
DOI: 10.1038/bjc.2017.173
|View full text |Cite
|
Sign up to set email alerts
|

CD47 overexpression is associated with decreased neutrophil apoptosis/phagocytosis and poor prognosis in non-small-cell lung cancer patients

Abstract: Background:Non-small-cell lung cancer (NSCLC) patients often exhibit neutrophilia, which has been associated with poor clinical outcomes. However, the mechanisms that lead to neutrophilia have not been fully established. CD47 is an antiphagocytic molecule that promotes neutrophil recruitment.Methods:Blood was collected from 50 treatment-naive patients with advanced NSCLC and from 25 healthy subjects. The frequency of CD66b+ cells and the expression of CD47 were determined by flow cytometry. Neutrophil apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 59 publications
3
73
2
Order By: Relevance
“…Inhibition of phagocytosis occurs when CD47 binds to signal regulatory protein alpha (SIRPα) expressed on the macrophage surface . CD47 overexpression is associated with growth and progression in various cancer types such as non‐Hodgkin's lymphoma, gastric, colorectal, bladder, breast cancer and NSCLC . We have previously reported that CD47 overexpression in whole‐blood samples from NSCLC patients is associated with poor OS, and its expression on neutrophil surface prevents apoptosis and phagocytic clearance of these cells .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of phagocytosis occurs when CD47 binds to signal regulatory protein alpha (SIRPα) expressed on the macrophage surface . CD47 overexpression is associated with growth and progression in various cancer types such as non‐Hodgkin's lymphoma, gastric, colorectal, bladder, breast cancer and NSCLC . We have previously reported that CD47 overexpression in whole‐blood samples from NSCLC patients is associated with poor OS, and its expression on neutrophil surface prevents apoptosis and phagocytic clearance of these cells .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 CD47 overexpression is associated with growth and progression in various cancer types such as non-Hodgkin's lymphoma, gastric, colorectal, bladder, breast cancer and NSCLC. [14][15][16] We have previously reported that CD47 overexpression in whole-blood samples from NSCLC patients is associated with poor OS, and its expression on neutrophil surface prevents apoptosis and phagocytic clearance of these cells. 14 Use of anti-CD47 antibodies for treatment of non-Hodgkin lymphoma, breast, bladder, and ovarian carcinomas has shown promising results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,35,36 Additionally, several studies have shown that high CD47 expression in tumors correlates with poor prognosis. 37 However, little is known about the role of CD47 in SS. Using TCR Vb staining to identify the dominant clone, we demonstrate that malignant lymphocytes (clonal Vb 1 CD4 1 ) express high levels of CD47 compared with nonmalignant lymphocytes in the same patient with SS.…”
Section: Discussionmentioning
confidence: 99%
“…In particular binding of CD47 to SIRPα induces ITIM phosphorylation and recruitment of SHP-1 and SHP-2 ultimately resulting in the inhibition of PMN apoptosis [77]. As such, increased PMN surface expression of CD47 is associated with a delay in apoptosis and poor prognosis in non-small cell lung cancer patients [78]. Finally, recent studies have demonstrated that sialylated erythrocyte surface glycans engage the inhibitory immunoreceptor Siglec 9 on circulating PMN to suppress activation and apoptosis [65].…”
Section: Introductionmentioning
confidence: 99%